2021
DOI: 10.1002/hep.31706
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitors in Combinations for Hepatocellular Carcinoma

Abstract: Analysis, and pitfalls of clinical trials using ex-situ liver machine perfusion: the International Liver Transplantation Society (ILTS) consensus guidelines transplantation. In press. 7) Marcon F, Schlegel A, Bartlett DC, Kalisvaart M, Bishop D, Mergental H, et al. Utilization of declined liver grafts yields comparable transplant outcomes and previous decline should not be a deterrent to graft use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Recently, the synergistic effect of systemic therapy and ICBs has been actively reported. VEGF/VEGFR signaling is associated with the immunosuppressive tumor microenvironment, in addition to its primary role in angiogenesis [ 39 ]. For example, VEGF/VEGFR signaling can suppress the function and differentiation of DCs, induce MDSCs [ 40 ].…”
Section: Evidence Of Current Icbs For Hccmentioning
confidence: 99%
“…Recently, the synergistic effect of systemic therapy and ICBs has been actively reported. VEGF/VEGFR signaling is associated with the immunosuppressive tumor microenvironment, in addition to its primary role in angiogenesis [ 39 ]. For example, VEGF/VEGFR signaling can suppress the function and differentiation of DCs, induce MDSCs [ 40 ].…”
Section: Evidence Of Current Icbs For Hccmentioning
confidence: 99%
“…3 Immunotherapy based on immune checkpoints has also been recently used in HCC. 5 However, its efficiency is limited to less than 20%. Therefore, there is a desperate and urgent need for comprehensive research on the mechanisms of development, progression, recurrence, metastasis, and resistance of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have suggested that immunotherapy based on immune checkpoint inhibitors is a promising therapeutic strategy for patients with advanced HCC, while its efficiency remains less than 20%. 5 Therefore, advances in the treatment of HCC are urgently needed, which requires comprehensive investigation on the pathogenesis of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…To verify the effects of TB/PTX@RTK-mediated chemo-PDT on the maturation of DCs, we extracted bone marrow cells from the femoral bone marrow of C57BL/6 mice according to previous method and used GM-CSF and IL-4 to differentiate and cultured them into immature bone marrow DCs (BMDCs) [4,10].…”
Section: Bmdc and Bmdc Maturation Assays In Vitromentioning
confidence: 99%
“…ICB therapies, especially programmed cell death protein 1 (PD-1)/programmed cell death ligand 1 (PD-L1) monoclonal antibodies (anti-PD-1/PD-L1), could relieve the immune restriction and restore T lymphocyte function in the tumor microenvironment (TME) [7,8]. Multiple types of anti-PD-1/PD-L1 monoclonal antibodies were recently approved by the FDA for the treatment of several types of malignancy, including rst-line therapy for advanced HCC [9,10]. However, the objective remission rate of ICB therapy in these patients was less than 20% [7,11,12], putatively because of the lack of su cient release of tumor-associated antigen (TAA) and in ltration of cytotoxic T lymphocytes (CTLs) [13].…”
Section: Introductionmentioning
confidence: 99%